2020
DOI: 10.31234/osf.io/hxqnd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Common Sense Model of Illness Self-Regulation: A Conceptual Review and Proposed Extended Model

Abstract: The common sense model of illness self-regulation outlines the dynamic processes by which individuals perceive, interpret, respond, and adjust, psychologically and behaviorally, to health threats and illness-related information. We present a revised version of the model that formally operationalizes key processes in the model and incorporates additional constructs and processes to provide a comprehensive explanation of how lay perceptions of health threats and illnesses impact coping responses and health-relat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 145 publications
0
21
1
5
Order By: Relevance
“…Moreover, the small sample size, due to the rarity of GTD, could limit the generalisability of our findings. Finally, although previous studies state that illness emotional representations do not correspond to a measure of general distress (Hagger & Orbell, 2020;Moss-Morris et al, 2002),…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, the small sample size, due to the rarity of GTD, could limit the generalisability of our findings. Finally, although previous studies state that illness emotional representations do not correspond to a measure of general distress (Hagger & Orbell, 2020;Moss-Morris et al, 2002),…”
Section: Discussionmentioning
confidence: 77%
“…The CSM postulates that illness representations have a direct and causal effect on coping behaviours, which, in turn, would influence illness outcomes. This has led to the development of a mediation model, in which coping mediates the effect of illness perception on health outcomes (Hagger & Orbell, 2003, 2020). However, significant inconsistencies exist across empirical research attempting to verify the hypothesised model and several studies have failed to support the mediation role of coping (Hagger & Orbell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of the sample with degreeand A-level education were in line with national data, 27 as was the proportion from ethnic minority backgrounds. 28 Women in the pre-screening age group (18)(19)(20)(21)(22)(23)(24) were under-represented in the study. However, the aim of the study was to make between-group comparisons rather than to draw generalisable conclusions about acceptability across the population.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we followed hypotheses derived from the Leventhal’s Common Sense Model of Self-Regulation [ 14 , 15 ] to examine the mediating roles of coping, psychological flexibility (i.e., the capacity of being open to difficult experiences and committed toward values-driven goals [ 16 ]) and prosociality (i.e., attitudes and/or behaviors that are intended to help and benefit others [ 17 ]) in the impacts of illness perceptions toward COVID-19 on mental health [ 18 ] (see Figure 1 ). Using cross-sectional survey data of 514 Hong Kong adults, we found that other than those known coping factors (i.e., seeking social support, problem-solving, avoidance and positive thinking), psychological flexibility and prosociality were the two higher-order response styles that significantly mediated the impacts [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study was to extend this single-site study evidence by investigating whether people in multiple worldwide regions exhibited similar coping patterns as of the Hong Kong sample. More specifically, in line with the theoretical bases derived from the Common Sense Model of Self-Regulation [ 14 , 15 ], we aimed to examine whether psychological flexibility and prosociality remained the fundamental aspects of protecting mental health among people across various geographical regions in the midst of COVID-19. In literature, only a few multi-country or multi-regional surveys have been conducted to document the prevalence of mental health illnesses in general public during the COVID-19 outbreak [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%